Rothia dentocariosa endocarditis with brain abscess and splenic abscess: case report and brief review - Zheng, Xue; Liu, Fang; Ma, Qiaoli; Li, Jing; Ma, Huiping (Frontiers in Cardiovascular Medicine, 2024)
Rothia dentocariosa is a conditionally pathogenic bacterium that may cause infective endocarditis (IE) in selected patients and give rise to a variety of clinical complications, albeit it is not a common IE pathogen. We present the case of a patient diagnosed with Rothia dentocariosa-associated IE secondary to influenza B and thrombocytopenic purpura. The blood culture revealed Rochebacterium caries, cardiac ultrasound detected vegetation, while brain and spleen abscesses manifested and progressively deteriorated. Despite a s uboptimal response to anti-infective therapy, the patient ultimately underwent aortic valve replacement.Discharge from the hospital was achieved upon control of the brain abscess and spleen abscess.